On the Applicability of a Precursor Derived from Organic Waste Streams for Bacteria-Based Self-Healing Concrete - Rossi, Emanuele; Vermeer, Chris M.; Mors, Renee; Kleerebezem, Robbert; Copuroglu, Oguzhan; Jonkers, Henk M. (Frontiers in Built Environment, 2021)
Bacteria-based self-healing concrete has the ability to heal cracks due to the bacterial conversion of incorporated organic compounds into calcium carbonate. Precipitates seal the cracks, theoretically increasing the service life of constructions. The aim of this paper is to propose a precursor for bacteria-based self-healing concrete derived from organic waste streams, produced is in line with the circular economy principle and ideally more affordable than other substrates. To verify the applicability of the proposed healing agent, some fundamental requirements of the proposed system are studied, such as its influence on functional properties, crack sealing capacity and evidence of bacterial activity in concrete.